Eksplorasi Etnomatematika pada Artefak Peninggalan Sejarah di Rumah Budaya Sumba - Ate, Arista Ngindi; Lubur, Dorothea Novia Ludo; Making, Samuel R. M.; Napu, Timotius W.; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to explore and understand the mathematical concepts found in historical artifacts at the Sumba cultural house museum. The method used in this study is qualitative with an ethnographic approach. Data collection is done through observation and interviews, and data analysis. The data collection techniques in this research are observation, interviews, and documentation. The main instrument in this study is the researcher themselves, and the tools used are observation guidelines, interview guidelines, and documentation. The data analysis process is carried out through several stages, namely data reduction, data presentation, and drawing conclusions or verification. The research results show that in the Sumba Cultural House museum there are various types of artifacts, including drums, ancient statues, jars, machetes, shields, gongs, tombstones, and various kinds of jewelry. The mathematical concepts applied to the artifacts in the Sumba Cultural House museum are the concepts of flat shapes and solid shapes. The flat shape concepts applied include squares, rectangles, triangles, kites, rhombuses, and circles. Meanwhile, the solid shape concepts applied include cubes, rectangular prisms, cylinders, and cones.